A teaching design of ecological class based on immersive virtual reality spatial fusion - Liu, Wenyuan (Frontiers in Psychology, 2022)
The immersive virtual reality (IVR) technology may stimulate a learner’s visual, auditory and tactile feelings directly to improve his/her learning efficiency. This is a pilot study for examining the effect of IVR spatial fusion on learning through teaching design of English as a foreign language based on the theories of Multimodal Learning Theory and Production-Oriented Approach (POA for short), put forward by Wen Qiufang (Wen, 2015). An ecological class is set up, extending classroom teaching to a wider three-layer space, including a physical layer (classroom-based), an information layer (internet-based) and a virtual-reality layer (VR-based). The teaching design of the Immersive Virtual-Reality Teaching Model (IVRTM) aimed at 1) making a spatial fusion learning environment with a series of online and offline learning activities, 2) acquiring the students’ attitude toward the IVRTM by questionnaire and interview, and 3) evaluating the feasibility and acceptability of the IVRTM through the Big-Data analysis. The findings of the research provide novel and preliminary references for teachers pursuing an effective teaching model based on spatial fusion learning.